Cartilage imaging significance, techniques, and new developments - Link, Thomas M. (Springer, New York, 2011)
This authoritative book provides state-of-the-art practices and new developments in the imaging of cartilage, associated pathologies, and repair procedures. With a main focus on MRI, major advances in cartilage imaging are put into clinical context relevant for radiologists, rheumatologists, and orthopedic surgeons. International experts provide their insights on cartilage pathologies associated with such conditions as osteoarthritis, osteochondral trauma, and cartilage repair. Morphological MRI techniques are outlined, including new sequences and high field imaging. Molecular imaging techniques able to characterize the biochemical composition of the cartilage matrix are discussed, such as T2 relaxation time, T1rho, and dGEMRIC methods. The first book of its kind, Cartilage Imaging: Significance, Techniques, and New Developments encompasses the full scope of knowledge in this rapidly evolving field. Identifying key techniques for characterizing disease processes as well as objectively and quantitatively evaluating the results of therapy, this outstanding resource is of benefit to all physicians interested in assessing cartilage disease and repair.